Electrophysiological correlates of critical-analytical thinking and executive functioning - Runyun, Şerife Leman (İstanbul Medipol Üniversitesi Sağlık Bilimleri Enstitüsü, 2018)
Critical thinking can be defined as purposeful and reasoned thinking that includes problem solving, decision making, estimating probabilities and formulating conclusions while using advanced skills for a particular situation and task. Critical thinking consists of two complementary elements; skills and dispositions. It is improvable and teachable. According to dual process theory, there are two thinking pathways; system 1 which is basic, fast and intuitive, system 2 which is more complex, slow and analytical. Since critical thinking can be considered as complex thinking, it might be related to system 2 thinking. Electrophysiology of our brain changes according to our mental states. Frontal EEG gamma activation is associated with insight and this might be a feature of critical thinkers. On the other hand, executive functions like inhibitory control and cognitive flexibility could be necessary to think critically. The aim of the study was to investigate electrophysiological correlates of critical thinking and explain critical thinking dispositions while considering 2 pathways. The first hypothesis was that system 2 thinking predicts critical thinking dispositions through frontal gamma activation. The second hypothesis suggested that executive functions also predict critical thinking dispositions. To test the model, structural equation modeling was used as the statistic method. According to results, the tendency to think critically can be predicted by system 2 thinking through frontal gamma band activity. However executive functions and critical thinking disposition was not significantly related.

Eleştirel düşünme; belirli bir durum veya görev için gelişmiş yetenekleri kullanırken; problem çözümü, karar verme, olabiliteleri hesaplama ve sonuçları formalize etmeyi kapsayan amaca yönelik, akıl yürütülmüş düşünme olarak tanımlanabilir. Eleştirel düşünme iki birbirini tamamlayıcı bölümden oluşur; yetenek ve yatkınlık. Geliştirilebilir ve öğretilebilir. İkili işleyiş teorisine göre, iki düşünme yolu vardır: basit, hızlı ve sezgisel olan sistem 1 ve daha karnaşık, yavaş ve analitik olan sistem 2. Eleştirel düşünme karmaşık düşünme olarak ele alınabileceğinden, sistem 2 düşünme ile ilişkili olabilir. Beynimizin elektrofizyolojik aktivitiesi zihinsel durumumuza göre değişiklik gösterir. Frontal EEG gamma aktivitesi içgörü ile ilişkilidir ve bu eleştirel düşünenlerin bir özelliği olabilir. Diğer bir yandan engelleyici kontrol ve bilişsel esneklik gibi yürütücü işlevler eleştirel düşünme için gerekli olabilirler. Bu çalışmanın amacı, eleştirel düşünmenin elektrofizyolojik korelatlarını incelemek ve eleştirel düşünme eğilimini 2 yolla açıklamak idi. Birinci hipotez, sistem 2 düşünmenin eleştirel düşünme eğilimini frontal gamma aktivasyonu yolu ile öngörebilmesidir. İkinci hipotez ise yürütücü işlevlerin de eleştirel düşünme eğilimini öngörebilmesidir. Modeli test etmek için yapısal eşitlik modeli istatistik yöntemi olarak kullanıldı. Sonuçlara göre eleştirel düşünmeye yatkınlık frontal gamma aktivasyonu yoluyla sistem 2 düşünme tarafından öngörülebilir. Ancak yürütücü işlevler ve eleştirel düşünme eğilimi anlamlı derecede ilişkili değildi.
Analitik düşünme, yürütücü işlevler ve elektrofizyolojik korelatları
Keywords: Analytical Thinking; Critical Thinking; Dual Process Theory; Electrophysiology; Executive Functions; Analitik Düşünme; Bilişsel İşlevler; Elektrofizyoloji; Eleştirel Düşünme; İkili İşleyiş Teorisi